عناصر استراتجيات الريادة وأثرها في ابعاد إبداع المنتج دراسة من وجهة نظر العاملين في مركز الأطراف الصناعية في الموصل - كتانة, خيري مصطفى; احمد أغا, احمد عوني (Recherches économiques et managériales; Vol. 11 (2012): RECHERCHES ÉCONOMIQUES ET MANAGÉRIALES(JUIN), 2015)
سعى البحث إلى تحديد تأثير عناصر استراتجيات الريادة في ابعاد إبداع المنتج في مركز الأطراف الصناعية في الموصل، إذ تعد عناصر استراتجيات الريادة من العناصر البالغة الأهمية في المنظمة. ولمحدودية الدراسات التي تناولت تأثير عناصر استراتجيات الريادة في ابعاد إبداع المنتج وبخاصة في البيئة العراقية على حد اطلاع الباحثين، فقد سعيا إلى تضمين بحثهم الحالي هذه الأبعاد بمتغيراتها ضمن إطار شمولي في محاولة لدراسة علاقة التأثير بينهما.  وبشكل عام يحاول البحث الإجابة عن التساؤل الآتي: ما طبيعة علاقات الارتباط والتأثير بين عناصر استراتجيات الريادة و ابعاد إبداع المنتج في المركز قيد البحث ؟ وتوصل البحث إلى مجموعة من الاستنتاجات أهمها: 1/ وجود علاقة ارتباط معنوية بين عناصر استراتجيات الريادة وابعاد ابداع المنتج .2/ وجود علاقة  تأثير معنوية لعناصر استراتجيات الريادة  في ابعاد أبداع المنتج.  واعتماداً على الاستنتاجات التي توصل إليها البحث فقد قدمت عدد من المقترحات المنسجمة مع هذه الاستنتاجات ومن أهمها: التأكيد على إدارة المركز زيادة الاهتمام  بعناصر استراتجيات الريادة و ابعاد إبداع المنتج بهدف تحسين المنتجات التي يقدمها المركز للزبائن المرتادين له. Abstract :  Research sought to determine the effect of the elements of Entrepreneurship strategies and Product Innovation dimensions in the Artificial Lamb center in Mosul, where these Strategic Entrepreneurship Elements are considered of the important Elements in the organization. Because of the Limitedness of studies which tackled the relationship between Strategic Entrepreneurship Elements and Product Innovation and especially in Iraq environment. The two researchers, research to include these dimensions within the framework of a holistic Bmngeradth research to include these dimensions within the framework of a holistic Bmngeradtha in an attempt to study the influence between them and in general trying to find the answer to the following question a in an attempt to study the influence between them and in general trying to find the answer to the following question: –      What is the nature of the relationship between Strategic entrepre - neurship elements and product innovation Dimension in the Center under study?   The study reached to a set of some important conclusions: 1/ There is a significant connection relationship between strategic entrepreneurship elements and Product innovation Dimension .2/ There is a significant effect for the activities of Strategic Entrepreneurship Elements in the Product Innovation Dimension . depending on the conclusions, which the study achieved, a set of harmonized suggestions with these conclusions have been presented ,one of the most important suggestions: Emphasis on the management of the Center increased attention to the elements of Entrepreneurship strategies and product innovation dimensions of creativity in order to improve products provided by the Center for customers usher him